![](https://www1.michaeldemichele.com/img/nextpage1.png)
Suggested: write the following cubes in expanded form (3/2x+1)3 - expand (3/2x+1)^3 - 4(x+3)-2x-1)=3x+3 - 2x/3+1=7x/15+3 - f(x)=2x+3 g(x)=1-2x y(x)=3 x prove that fo(goh)=(fog)oh - find the discriminant of the equation 3x^2-2x+1/3=0 - 2x/3+1=7x/15+3 solve and check - 3(2x-1)=-2(x+3) - 3x-5y+1=0 2x-y-3=0 graph - find the term independent of x in the expansion of (3/2x^2-1/3x)^6 - 1/2x+1/3y=2 and 1/3 x+1/2y=13/6 - 2x/x-3+1/2x+3+3x+9/(x-3)(2x+3)=0 - 3(x-3)=5(2x-1) solve - 2x+y+z=1 x-2y-z=3/2 3y-5z=9 - (3 2x+1)3 Browse related:
privacy contact
Copyright 2017 bapse
bapse is powered by Google and Youtube technologies
Thank you, for using bapse.
This site was designed and coded by Michael DeMichele,
and is being used as a portfolio demonstration. View more.